A Survey on Underwater Fish Species Detection and Classification - Syreen, R Fathima; Merriliance, K (International Journal of Computer Sciences and Engineering, 2025)
Fish species recognition is a challenging task for research. Great challenges for fish recognition appear in the special properties of underwater videos and images. Due to the great demand for underwater object recognition, many machine learning and image processing algorithms have been proposed. Deep Learning has achieved a significant results and a huge improvement in visual detection and recognition. This paper mainly reviews some techniques proposed in past years for automatic fish species detection and classification.